Urban development impacts on natural ecosystems in urban protected areas of Tehran province, Iran - Parvaneh Sobhani (Heliyon)
Urban development, especially in metropolises, is effective in threatening natural ecosystems and Protected Areas (PAs). Consequently, the current study seeks to explore the interrelationships between urban development and its environmental impacts on PAs. To achieve this, a set of main indicators has been evaluated to assess the progression of urbanization within the Jajrud protected set. According to the results, the highest weight value among the urban development indicators is related to spatial urbanization. This is attributed to the establishment of industrial sites, excessive mining activities, development of various infrastructures, expansion of transportation networks and roads, as well as the widespread growth of tourism activities. Moreover, the outcomes of secondary indicators suggest that the growth of urban regions and the rise of total fixed-asset assets over the past two decades are fundamental factors contributing to urban development in the Jajrud protected set. Likewise, the path of urbanization has increased from 2000 to 2021, and urbanization indicators of spatial and economic have increased most compared. In conclusion, the analysis of the mutual impact of urban development on PAs indicates that, according to a double exponential curve, a direct and significant relationship between urban development and its impacts on the environment is visible. This implies that regions characterized by lower levels of urbanization could have better opportunity for environmental quality. Hence, managers and planners should give greater consideration to the significance of environmental protection and socio-economic issues in the decision-making process of urban plans, particularly in urban areas with extensive urbanization development such as Tehran.